2016
DOI: 10.1159/000444591
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Spinal Dorsal Root Inhibits Reflex Bladder Contraction and External Urethra Sphincter Activity: Is This How Sacral Neuromodulation Works?

Abstract: Introduction: Using a rat model, we aimed to confirm the inhibitory effect of dorsal spinal root (afferent) stimulation and test if bilateral stimulation is more effective than unilateral stimulation. External urethral sphincter (EUS) electromyography (EMG) is also assessed in conjunction with cystometrogram. Materials and Methods: Eighteen female Sprague-Dawley rats were tested following urethane anesthesia. Via urethral catheterization, the bladder was infused with normal saline to evoke rhythmic bladder ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In the CMG model, peripheral nerve stimulation to anesthetized animals prolonged the latency of urination, indicating an increased volume threshold of the micturition reflex (Su et al, ; Choudhary et al, ; Jiang et al, ; Kadow et al, ; Rogers et al, ; Bandari et al, ; Bansal et al, ; Fuller et al, ; Uy et al, ; Zhang et al, ). In the RMC model, peripheral nerve stimulation abolished periodic intravesical pressure changes, reflecting suppression of the micturition reflex at a volume that was previously supra‐threshold (Su et al, ; Kovacevic and Yoo, ; Su et al, ; Onda et al, ; Ren et al, ). Taken together, these findings indicate that electrical stimulation of peripheral nerves is capable of inhibiting detrusor muscle contractions.…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CMG model, peripheral nerve stimulation to anesthetized animals prolonged the latency of urination, indicating an increased volume threshold of the micturition reflex (Su et al, ; Choudhary et al, ; Jiang et al, ; Kadow et al, ; Rogers et al, ; Bandari et al, ; Bansal et al, ; Fuller et al, ; Uy et al, ; Zhang et al, ). In the RMC model, peripheral nerve stimulation abolished periodic intravesical pressure changes, reflecting suppression of the micturition reflex at a volume that was previously supra‐threshold (Su et al, ; Kovacevic and Yoo, ; Su et al, ; Onda et al, ; Ren et al, ). Taken together, these findings indicate that electrical stimulation of peripheral nerves is capable of inhibiting detrusor muscle contractions.…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%
“…In studies examining the effects of peripheral nerve activation by electrical stimulation on urinary bladder functions, stimulation is commonly applied to the tibial nerve, pudendal nerves, or the sacral nerves (Su et al, 2013a(Su et al, , 2013b(Su et al, , 2015Kovacevic and Yoo, 2015;Choudhary et al, 2016;Jiang et al, 2016;Kadow et al, 2016;Onda et al, 2016;Ren et al, 2016;Rogers et al, 2016;Bandari et al, 2017;Bansal et al, 2017;Fuller et al, 2017;Uy et al, 2017;Zhang et al, 2017). Hence, somatic afferents sending sensory inputs to spinal levels near pelvic nerve efferent outputs innervating the bladder are generally targeted for stimulation.…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%
“…There have been several reports of improvement in LUT dysfunction using transcutaneous stimulation (Walsh et al, 2001;Barroso et al, 2013;Quintiliano et al, 2015) in addition to implantable devices, as well as a study reporting no effect on NDO in a small MS cohort. An acute inhibitory effect of SNS on NDO has been shown in several animal studies (Snellings and Grill, 2012;Su et al, 2012;Ren et al, 2016). Using non-invasive magnetic stimulation techniques, NDO has been acutely suppressed in humans with SCI (Sheriff et al, 1996), and interestingly, early application of implanted, continuous, SNS in the acute stages of SCI has prevented the development of NDO in the chronic phase of injury (Sievert et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Spinal Stimulation, using stimulation of the dorsal surface or dorsal roots of the spinal cord at the level of the T12 vertebra has had promising reports of improved lower limb and bladder control from both pre-clinical and clinical studies (Harkema et al, 2011;Hofstoetter et al, 2014;Gerasimenko et al, 2015;Gad et al, 2016;Ren et al, 2016;Herrity et al, 2018). Previous studies of epidural stimulation conducted with MS participants have reported acute improvements in LUT function (Meglio et al, 1980), including in the suppression of detrusor contractions with some carry-over effect noted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these classical approaches, efforts are being made to intervene closer to the cause by influencing the damaged innervation of the lower urinary tract [1]. Neurostimulation is understood as directly affecting the target organ, neuromodulation as affecting the nerve center by stimulating its afferent pathways and reinnervation as restoring nerve function with the aid of another, undamaged nerve.…”
Section: Introductionmentioning
confidence: 99%